2007
DOI: 10.1038/sj.ki.5002098
|View full text |Cite
|
Sign up to set email alerts
|

Donor age intensifies the early immune response after transplantation

Abstract: Increasing donor age is associated with reduced graft function. We wondered if donor age may not only affect intrinsic function but also alter the immune response of the recipient. Kidneys from young and old F-344 rats (3 vs 18 months) were transplanted into bilaterally nephrectomized young Lewis recipients and compared with age-matched controls (follow-up: 6 months). Renal function and structural changes were assessed serially in both native kidneys and allografts. Host alloreactivity, graft-infiltrating cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
49
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 46 publications
4
49
1
Order By: Relevance
“…Some studies have demonstrated the potential of immunosuppressive induction therapy to reduce the disparity between negative outcomes of extended versus standard criteria (including deceased vs living) donor kidneys [20][21][22]. Khalafi-Nezhad et al found no distinct difference in rejection rates from deceased or living donor kidney recipients [23].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have demonstrated the potential of immunosuppressive induction therapy to reduce the disparity between negative outcomes of extended versus standard criteria (including deceased vs living) donor kidneys [20][21][22]. Khalafi-Nezhad et al found no distinct difference in rejection rates from deceased or living donor kidney recipients [23].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, autophagy dysfunction is a recurring feature upon ageing [68]. As such, autophagy dysfunction could also partially account for the higher degree of early immune responses after kidney transplantation of renal grafts of older rat donors [69]. The generation of proximal tubule-specific Atg5-and Atg7-knockout mice has largely overcome the problem of the non-specificity of the chemical autophagy modulators.…”
Section: Transplantation/ischemiamentioning
confidence: 99%
“…4,5 Analysis of United Network of Organ Sharing registry by Gill and associates demonstrated a higher risk for acute rejection and trend toward poor allograft survival in elderly kidney transplant recipients who received induction with IL-2B agents compared with r-ATG. 15 The authors recommended the use of r-ATG in elderly patients receiving high-risk donor kidneys including ECD or donation after cardiac death kidneys and kidneys with cold ischemia time > 24 hours.…”
Section: Sabiha M Hussain Et Al/experimental and Clinical Transplantmentioning
confidence: 99%
“…3 Renal allografts from older donors have impaired ability to repair tissue injury, leading to persistent inflammation and increased immune recognition. 4 A multivariate analysis by de Fitzer and associates showed increased incidence of acute rejection episodes in patients receiving a renal allograft from donors older than age 50 years. 5 Because ECD kidneys appear more immunogenic, it is intuitive to think that enhanced immunosuppression such as steroid maintenance would be beneficial in recipients of such kidneys.…”
Section: Introductionmentioning
confidence: 99%